Branching ratio measurements of B → J/ψηK and B± → D0K± with D0 → π+π-π0 - Zeng, Qinglin, author; Wilson, Robert J., advisor; Toki, Walter H., committee member; Harton, John L., committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2005)
Results are presented for the decays of B → J/ψηK and B± → DK±, respectively, with experimental data collected with BABAR detector at PEP-II, located at Stanford Linear Accelerator Center (SLAC). With 90 x 106 BB events at the Y(4S) resonance, we obtained branching fractions of B(B± → J/ψηK±) = [10.8±2.3(stat)±2.4(syst)] x 10-5 and B(B0 → J/ψηK0S) = [8.4±2.6(stat)±2.7(syst)] x 10-5; and we set an upper limit of B[B± → X(3872)K± → J/ψηK±] < 7.7 x 10-6 at 90% confidence level. The branching fraction of decay chain B(B± → DK± → π+π-π0K±) = [5.5±1.0(stat)±0.7(syst)] x 10-6 with 229 x 106 BB events at Y(4S) resonance, here D represents the neutral D meson. The decay rate asymmetry is A = 0.02±0.16 (stat)±0.03(syst) for this full decay chain. This decay can be used to extract the unitarity angle y, a weak CP violation phase, through the interference of decay production of D0 → π+π-π0.
Branching ratio measurements of B meson decays to J/psi meson eta meson kaon and charged B meson decays to neutral D meson charged kaon with neutral D meson decays to positive pion negative pion neutral pion
Keywords: particle physics